Pelayanan Fisioterapi Melalui Pemeriksaan Mini-Mental State Examination Untuk Menilai Fungsi Kognitif Lansia di RW 8 Kelurahan Tanjung Rejo Kota Malang - Nidya Andini Netakusuma; Dimas Sondang Irawan; Endang Listyowati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Impaired cognitive function is still a serious health problem that can cause psychological and socio-economic impacts in the form of social isolation and financial difficulties, delayed mobility, and worsening of other symptoms as well as reducing quality of life. As a basis for elderly health services, it is hoped that healthy elderly people will remain healthy. by optimizing physical, mental, cognitive and spiritual functions, through promotive and preventive efforts, including elderly empowerment activities. This counseling aims to assess cognitive function using the Mini Mental State Examination (MMSE) in the elderly at Posyandu for the elderly RW 8 Tanjung Rejo, Malang City. The method given is an examination using the Mini Mental State Examination (MMSE) questionnaire. The counseling process went smoothly. The results of the examination showed that the majority of elderly people had normal cognitive conditions. A good lifestyle can reduce the risk of dementia.